A new species of Paratheuma (Araneae: Dictynidae) from Southwestern Asia and transfer of the genus. Issue 2 (2nd April 2016) - Zamani, Alireza; Marusik, Yuri M.; Berry, James W.
Abstract : The marine spider genus Paratheuma Bryant, 1940 is recorded in southwestern Asia for the first time, and a new species, P . enigmatica sp. n. is described from southern and southeastern Iran on the basis of both sexes. Based on morphological and molecular evidence, the genus is transferred from Desidae to Litisedinae, Dictynidae. http://www.zoobank.org/urn:lsid:zoobank.org:pub:BC5B70CB-E6C9-4624-8BE8-22FF14AF6DC7